2015
DOI: 10.1111/jgs.13646
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Reduce Ventilator‐Associated Pneumonia in Individuals on Long‐Term Ventilation by Introducing a Customized Bundle

Abstract: A modified bundle successfully decreased VAP rates in chronically ventilated elderly LTCF residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
8
0
3
Order By: Relevance
“…In our study, it was proven that VAP development speed was 43% lower with the controlled group and ventilator bundle adaptation control reduces VAP development by 75%. Reading the related literature, it can be seen that there are a lot of studies that supports our study, and these studies show that with proper application of ventilator bundles [4,12,14,15,[19][20][21][22][23][24][25][26][29][30][31][32][33][34][35] and higher adaptation of the staff to them [14,15,18,20,23,24,26,[31][32][33][34][35][36][37][38] VAP rate and speed decreases. However, diversely from our study, ventilator application bundles of different approaches and various numbers of them were utilized in those studies [4,12,14,15,[19][20][21][22][23][24][25][26]…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In our study, it was proven that VAP development speed was 43% lower with the controlled group and ventilator bundle adaptation control reduces VAP development by 75%. Reading the related literature, it can be seen that there are a lot of studies that supports our study, and these studies show that with proper application of ventilator bundles [4,12,14,15,[19][20][21][22][23][24][25][26][29][30][31][32][33][34][35] and higher adaptation of the staff to them [14,15,18,20,23,24,26,[31][32][33][34][35][36][37][38] VAP rate and speed decreases. However, diversely from our study, ventilator application bundles of different approaches and various numbers of them were utilized in those studies [4,12,14,15,[19][20][21][22][23][24][25][26]…”
Section: Discussionsupporting
confidence: 67%
“…In order to gather data, (1) Introductory Features Form, (2) VAP Prevention Bundle Application List which was designed in accordance with the current literature [4,[12][13][14][15][16][17][18][19][20]24]and (3) VAP Prevention Bundle Control List were utilized.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…121,141 Data from 22 studies with aggregated data for VAP are shown in Supplementary Table S5 12 13 , 27 , 28 ,35 ,41,48,49,52,53,59,64,75,120,127,128,131,136,139,140,144,152 Changes in VAP rates or proportions in these reports ranged between 100% reduction and a 17% increase (statistical significance not reported).
Fig. 5Incidence rate ratios (IRRs) from random-effects models for ventilator-associated pneumonia (VAP) in uncontrolled before-and-after studies stratified by country economic income status.
…”
Section: Resultsmentioning
confidence: 99%
“…121,141 Data from 22 studies with aggregated data for VAP are shown in Supplementary Table S5. 12,13,27,28,35,41,48,49,52,53,59,64,75,120,127,128,131,136,139,140,144,152 Changes in VAP rates or proportions in these reports ranged between 100% reduction and a 17% increase (statistical significance not reported).…”
Section: Ventilator-associated Pneumoniamentioning
confidence: 93%